Correlation Between Hemodynamic Status and Survival Rates in Severe Burn Patients During Emergency Phase - Rahagia, Rasi; Anggrasari, Anggun Pranessia (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Disturbance in the hemodynamic status in the severe burn is a serious problem that occurs most frequently in the emergency phase. The hemodynamic status of burn patients is influenced by the physiological response of the body to the characteristics of the burn severity. This study aimed to analyze the relationship between the hemodynamic status and the survival rate of severe burn patients in the emergency phase at RSSA Malang. This research was a documentary analysis employing a retrospective design on 80 samples of the medical records in RSSA Malang in the last 2 years. The results of the relationship analysis showed that the factors associated with the survival rate were the systolic blood pressure (p = 0.000) and respiratory rate (p = 0.000). Thus, monitoring the hemodynamic status in the emergency phase is vital to evaluate the effectiveness of therapy in increasing the survival rate in severe burn patients.